Controlling hydroelastic instability of hull panels through structural inhomogeneity - Tan, Ben Hoea; Lucey, Anthony; Pitman, Mark (The Royal Institution of Naval Architects, 2011)
The hydroelastic stability of flexible panels exposed to high-velocity mean flow is of fundamental significance to hull design. It is well-known that a simply-supported flexible panel exposed to increasingly high velocities will succumb to a divergence or static buckling-type instability at a particular critical flow speed. At a higher flow speed the panel will experience violent oscillatory flutter-type instability. In this paper we briefly present a recently developed approach and its new extension to theoretical modelling of the fully coupled interaction between a simply-supported flexible panel and a fluid flow. Structural inhomogeneity is incorporated as an additional single-spring support to the panel. The dependence of instability onset flow speeds, and the forms of divergence and flutter instabilities, upon the added spring stiffness and its location are then investigated. Results show that this particular form of structural inhomogeneity can be very effective in controlling the critical flow speed. This suggests a practicable strategy for designing out damaging hydroelastic effects in high-speed marine applications.